The Shāfa’ī Doctrine of Ḥadīth-e-Mursal - Attorah, Abdul Aziz Husain (Journal of Islamic and Religious Studies, 2022)
Imam Al Shāfa’ī, is distinguished by his services in ḥadīth as there is no one similar to him in it, and this is not strange for Al Shāfa’ī, as he is one of the renowned jurists and scholars of ḥadīth. His famous book “Al-Risālah” is an essential book of Islamic jurisprudence and is also considered a foundation book in ‘Ulūm al-Ḥadīth. There is no comprehensive research on the opinion of Imam Al Shāfa’ī on Ḥadīth-e-Mursal, which fulfills his opinion on it and the conditions for its implementation, except for research by Dr. Ibrahim Mulla Khāṭir. This research completes the flaws found in previous studies and adds some explanation, clarification, and discussion to some of the opinions about the Mursal. The study concludes that Imam Al Shāfa’ī accepts the Mursal of the senior Tāba’īn with five conditions; on the contrary, he does not accept the Mursal of junior Tāba’īn for a few reasons. As for the Mursal of the Companions, it is more likely that he accepts them as Ibn Burhān said that the Shāfa’ī doctrine does not permit to invoke of the Marāsīl except for the Companions and Sa’īd bin Al Musayyib.